Expel students involved in sex excapades, says exco man - The Star (Star Publications (M) Bhd, 2010)
A Terengganu lawmaker has called for the expulsion of undergraduates at a University in Terengganu, suspected of being involved in distributing sex toys and operating a prostitution ring.